Transfer, Exchange, Entanglement—And What Else? (KULT_online, 2011)
'Cultural exchange' is on everyone’s lips and takes up much space in the humanities—such as in the historiography of Early Modern times. Over the last 20 years different theories and methods have been developed which are summarized under the umbrella of the cultural transfer studies (Kulturtransferforschung). The exchange of knowledge, material goods or persons is increasingly understood as a complex process in which the objects of transfer are in a permanent state of negotiation. Not only the transferred object is constantly changing, but also the 'sender' and the 'recipient,' which could be seen as a construct of several transfer processes. The authors of the present collected volume see this topic from different angles. Alongside theoretical discussions, some empirical cases are presented which point to the full range of cultural exchange. The contemporary historian Michael Werner and the British cultural historian Peter Burke offer a view beyond the German Early Modern field. The agenda of the opus is to take stock of the subject and to give new impetus for research. In recent years the approach has changed from a one-way transfer to a more complex transfer process. This is shown explicitly in the contributions.